Dual combination synchronization scheme for nonidentical different dimensional fractional order systems using scaling matrices - Yadav V.K.; Srivastava M.; Das S. (My University, 2025)
In this chapter the dual combination synchronization has been studied among different dimensional fractional order systems by using scaling matrices. The dual combination synchronization scheme for different dimensional fractional order systems is also developed. The fractional order time derivative is described in Caputo sense. During synchronization the control functions are designed based on fractional order Lyapunov stability theory and using a new lemma which is given for fractional order Lyapunov function. Numerical simulation and graphical results clearly exhibit that the proposed procedure is easy to implement and reliable for dual combination synchronization for nonidentical and different dimensional fractional order chaotic systems. © 2018 Elsevier Inc. All rights reserved.